Design, synthesis and evaluation of novel 5-phenylpyridin-2(1H)-one derivatives as potent reversible Bruton's tyrosine kinase inhibitors. Issue 2 (15th January 2015) - Zhao, Xinge; Xin, Minhang; Huang, Wei; Ren, Yanliang; Jin, Qiu; Tang, Feng; Jiang, Hailong; Wang, Yazhou; Yang, Jie; Mo, Shifu; Xiang, Hua
Graphical abstract